Digital Transformation: Overcoming Systemic Barriers to the Distribution of Educational Operational Assistance (BOP) Through an Artificial Intelligence (AI)-Based Fast-Track Verification Scheme - I Gusti Ngurah Gita Senjaya (JURNAL ILMIAH GEMA PERENCANA, 2026)
Digital transformation in the national education sector is inevitable to improve the efficiency of public assistance management. However, at the level of private religious education, such as Pratama Widyalaya, this transition faces systemic obstacles in the form of a digital divide and data synchronization failures. Key issues identified include fragmentation of data reference codes between ministries, low digital literacy among senior management demographics, and limited internet infrastructure in remote areas, which has led to delays in the disbursement of Educational Operational Assistance (BOP) for up to two quarters. This policy research aims to formulate an innovative solution through the implementation of an Artificial Intelligence (AI)-based Fast-Track verification scheme. The policy methodology used is a descriptive qualitative approach with Evidence-Based Policy Making (EBPM) analysis techniques, which integrates secondary data from the Central Bureau of Statistics (BPS), a literature review of previous research journals, and an organizational risk analysis. Through stakeholder mapping and change management analysis, this policy evaluates the effectiveness of using Machine Learning algorithms for automated document validation and real-time cross-platform data synchronization. The analysis results show that the AI ​​scheme can significantly reduce administrative burdens and minimize human error. The policy conclusion recommends the issuance of a Director General of Hindu Community Guidance Decree to legitimize AI-based verification as a strategic instrument to ensure the financial stability of religious educational institutions through timely, accurate, and equitable distribution of funds.